2006
DOI: 10.3748/wjg.v12.i23.3636
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance 1 gene in inflammatory bowel disease: A meta-analysis

Abstract: The MDR1 gene is an attractive candidate gene for the pathogenesis of inflammatory bowel disease (IBD) and perhaps response to therapy, with evidences at both functional and genetic levels. Its product, the P-glycoprotein (P-gp) functions as a transmembrane efflux pump thus influencing disposition and response of many drugs, some of whom (i.e. glucocorticoids) central to IBD therapy. In addition P-gp is highly expressed in many epithelial surfaces, included gastrointestinal tract (G-I) with a putative role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 75 publications
2
91
0
2
Order By: Relevance
“…In contrast, the effects on cyclosporine pharmacokinetics are more complex: Overall, there was no effect of the c.3435C>T ABCB1 polymorphism on the pharmacokinetic parameters, although the total cyclosporine bioavailability (AUC 0-12 ) was slightly reduced (table 3) [101]. Furthermore, the c.3435C>T polymorphism was found to be associated with a minimal increase in the risk for ulcerative colitis or breast cancer in Caucasians [102][103][104]. Taken together, the c.3435C>T…”
Section: Mdr1 (Abcb1)mentioning
confidence: 98%
“…In contrast, the effects on cyclosporine pharmacokinetics are more complex: Overall, there was no effect of the c.3435C>T ABCB1 polymorphism on the pharmacokinetic parameters, although the total cyclosporine bioavailability (AUC 0-12 ) was slightly reduced (table 3) [101]. Furthermore, the c.3435C>T polymorphism was found to be associated with a minimal increase in the risk for ulcerative colitis or breast cancer in Caucasians [102][103][104]. Taken together, the c.3435C>T…”
Section: Mdr1 (Abcb1)mentioning
confidence: 98%
“…Even though C3435T is a silent SNP, early studies [20] showed a decrease in duodenal MDR1 protein expression. Reasons for its effects are still subject of debate [21] and a possible link between this SNP and IBD is also inconclusive [12].…”
Section: P-glycoprotein (P-gp Mdr1)mentioning
confidence: 99%
“…There are indications that the MDR1 G2677T allele is in linkage disequilibrium with C3435T, offering a possible explanation for loss of activity associated with this silent SNP [22]. MDR1 G2677A is not equally well understood as its prevalence is very low (around 1%) [12] and high sample sizes are needed to give valid estimates. Some authors therefore chose to exclude it in their studies [23,24].…”
Section: P-glycoprotein (P-gp Mdr1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic predisposition to inflammatory bowel diseases has been well-established through epidemiological studies and genome-wide linkage analyses; however, the accountable genes require further analyses (4). Therefore, the association between the polymorphism of various genes and UC has been studied previously (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%